Microsatellite evolution and population genetics of ancient and living Adélie penguins in Antarctica : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biological Sciences at Massey University - Shepherd, Lara Dawn (Massey University, 2001)
Microsatellites are widely used as genetic markers for examining a variety of biological questions. Despite their widespread use, little is known about the processes by which they evolve. An accurate understanding of these processes is essential for their correct use as population genetic markers. In this study, microsatellite loci from both living and cryopreserved (AMS 14C dated at up to 6424 years BP ±80) Antarctic Adélie penguins (Pygoscelis adeliae) were examined in order to gain insights into temporal population genetics and the evolution of microsatellite loci. Firstly, ancient DNA extracted from Adélie penguin subfossil bones was found to be extremely well-preserved and readily allowed the amplification of single-copy nuclear microsatellite DNA. Genotyping six microsatellite loci in ancient and living samples from three populations of Adélie penguins in the Terra Nova Bay region allowed a comparison of genetic change over time. Although the ancient sample sizes were limiting, several statistical tests indicated that the ancient and living populations from Inexpressible Island were genetically distinct. In addition, differentiation was also inferred between the three ancient populations that were examined, which is in contrast to the lack of differentiation found between the living populations. These genetic changes may be a result of population expansion out of ice-age refugia since the Last Glacial Maximum. To study microsatellite evolution over a substantial time period, up to 500 living and 100 cryopreserved Adélie penguins were genotyped at six microsatellite loci. No novel electromorph alleles were detected in the ancient samples. Numerous alleles were sequenced from four of these loci in both Adélie penguins and several other species of penguin (Spheniscidae). Analysis of these sequences provided an insight into the mutational processes occurring at these loci. In particular, these allele sequences revealed extensive size homoplasy, both within Adélie penguins and between penguin species. At one locus, variation in the flanking region allowed discrimination between the mechanisms proposed for length change at microsatellite loci. Slippage was the most plausible mechanism for length change. In this same locus, instability was observed in the region bordering the repeat tract with a transversional bias predominating. This bias may be a caused by inaccurate DNA replication resulting from structural features of DNA.
Keywords: Adélie penguin; Molecular genetics; Evolutionary genetics; DNA Analysis